2022
DOI: 10.1136/oemed-2021-108111
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relationship between melatonin patterns and methylation in circadian genes among day shift and night shift workers

Abstract: ObjectivesMechanisms underlying the carcinogenicity of night shift work remain uncertain. One compelling yet understudied cancer mechanism may involve altered DNA methylation in circadian genes due to melatonin secretion patterns. The objective of this study was to explore the relationship between melatonin secretion patterns and circadian gene methylation among day and night shift workers.MethodsFemale healthcare employees (n=38 day workers, n=36 night shift workers) for whom we had urinary 6-sulfatoxymelaton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Although the MTNR1A gene is thought to be related to ovine estrus or reproduction, it has not been studied from the perspective of DNA methylation in the promoter region. One previous study reported that the alteration of DNA methylation in the putative promoter region of the MTNR1A gene may induce pathways that increase cancer risk for nightshift workers [ 40 ]. In our present study, using a luciferase reporter gene, we constructed vectors carrying different lengths of the MTNR1A gene promoter sequence and identified the core promoter region to be in the 540 bp region upstream of the TSS ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the MTNR1A gene is thought to be related to ovine estrus or reproduction, it has not been studied from the perspective of DNA methylation in the promoter region. One previous study reported that the alteration of DNA methylation in the putative promoter region of the MTNR1A gene may induce pathways that increase cancer risk for nightshift workers [ 40 ]. In our present study, using a luciferase reporter gene, we constructed vectors carrying different lengths of the MTNR1A gene promoter sequence and identified the core promoter region to be in the 540 bp region upstream of the TSS ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of systemic mediators (i.e., myokines and osteokines) in serum from those working during the day vs. night could be evaluated to gain insights into interactions with circadian rhythm mediators regarding levels. Evidence for this concept has been reported by James et al [ 166 ] and Ritonja et al [ 167 ], indicating that shift work can lead to alterations in circadian rhythm mediator expression as well as epigenetic alteration to relevant genes. For others, it may even be possible to perform such studies using individuals who work alternating shift work, and thus potentially addressing individual variation in responsiveness.…”
Section: Further Testing the Acute “Conditioning/deconditioning” Hypo...mentioning
confidence: 95%
“…The latest research has highlighted that changes in melatonin synthesis and the circadian rhythm are related to cancer development [ 110 , 111 , 112 ]. There is a relationship between disturbances in the circadian rhythm and genomic instability [ 113 , 114 ].…”
Section: Melatonin and Its Role In Dna Methylationmentioning
confidence: 99%
“…The studies involving night shift workers indicated that melatonin secretion is associated with distinctive methylation pattern of genes implicated in the circadian cycle [ 112 , 121 ]. A cross-sectional study, including nurses and midwives who worked day shifts and rotating night shifts, showed differential blood-based DNA methylation statuses in the circadian genes in the latter group [ 121 ].…”
Section: Melatonin and Its Role In Dna Methylationmentioning
confidence: 99%